PEMBINAAN MAJELIS TAKLIM DALAM MENANAMKAN PEMAHAMAN KEAGAMAAN MASYARAKAT DESA PARINGGONAN PADANG LAWAS - Romaito Sasmita Siregar; Sawaluddin Siregar; Andi; Hendra Gunawan (Yayasan Baitul Hikmah al-Zain, 2025)
This community service aims to provide guidance and empowerment to the community of Paringganon Village, Ulu Barumun District, Padang Lawas Regency. Majlis Ta'lim is a non-formal educational institution that has an important role in fostering and developing understanding of Islam in the community. The community service method is carried out as a facilitator and resource person and as feedback interviews and observations are conducted to obtain a comprehensive picture of knowledge regarding the role of Majlis Ta'lim. The results of the Community Service show that Majlis Ta'lim has a significant influence in improving the understanding and religious practices of the community of Paringganon Village. Through religious study activities, religious lectures, and group discussions, Majlis Ta'lim contributes to increasing religious awareness and the formation of Islamic character among the community. In addition, Majlis Ta'lim also functions as a social media that strengthens social ties between villagers, thus creating a harmonious environment and increasing solidarity between residents. However, this Community Service also found several challenges faced by Majlis Ta'lim, such as limited resources and lack of active participation from young people. Therefore, there needs to be an effort to increase capacity and develop more inclusive programs in order to reach all levels of society. Thus, it is hoped that Majlis Ta'lim can continue to contribute positively to the religious and social life of the Paringganon Village community.